ANOTHER LOOK AT TYPE 2 DIABETES PATIENT: "DIALOGUE" STUDY RESULTS - I. E. Sapozhnikova; E. I. Tarlovskaya; E. N. Anufrieva; A. A. Sobolev; E. V. Rodygina (Столичная издательская компания, 2016)
Aim. To evaluate factors affecting hypoglycemic therapy in patients with type 2 diabetes mellitus (DM2) in real clinical practice. Material and methods. 200 patients with DM2, who consented to take part in the questionnaire, were examined. Questionnaire data evaluation and clinical examination was performed as well as plasma levels of glucose, glycosylated hemoglobin (HbA1c) and lipids estimation. Results. Low rate of diagnosed DM2 complications especially nephropathy was observed. 68% of patients had high level of glycosylated hemoglobin (HbA1c) because of their knowledge lack as well as inadequate glucose self-monitoring or it's absent and uncommon combined glucose-lowering therapy. Depression was revealed in 43,5% of patients, especially in patients with chronic DM2 complications. Low incidence of depression was associated with good patient knowledge about DM2. Well informed patients had lower score according to CES-D scale than patients with DM2 complications. Conclusion. Appropriate drug therapy, patients' education, early depression diagnosis and treatment are necessary to improve glycemic control in DM2 patients.